Academic Readiness and University–Industry Collaboration in Online and Flexible Learning Pathways: A Multi-University Case Study in Indonesia - Jamal Fakhri; Farida Farida; Raden Roro Atmim Nurona; Marzuki Marzuki; M. Indra Saputra; Muhammad Aridan (Online Learning In Educational Research (OLER), 2026)
Online and Flexible Learning Pathways (OFLPs) have emerged as a strategic approach for strengthening graduate employability by connecting academic learning with authentic workplace experiences. However, their successful implementation depends not only on student participation but also on institutional readiness, effective supervision, digital infrastructure, and sustainable university–industry partnerships. This study explored academic readiness and university–industry collaboration in OFLP implementation across three Indonesian universities. A qualitative-dominant multi-case study with an embedded descriptive survey design was employed. Data were collected through open-ended questionnaires, in-depth interviews, and participant observation, and analyzed using descriptive statistics and thematic analysis supported by NVivo 14. The findings indicate that students generally perceived OFLPs as relevant to industry needs and beneficial for developing critical thinking, problem-solving, and professional skills. Nevertheless, challenges related to time management, structured mentoring, faculty workload, digital supervision, and partnership coordination remained substantial barriers to effective implementation. The study conceptualizes academic readiness as a collective institutional capability shaped by learners, faculty, digital ecosystems, and external partners. These findings provide practical guidance for designing sustainable OFLPs through integrated governance, structured mentoring, coordinated academic planning, and stronger university–industry collaboration.